UPAYA MEREDUKSI KECANDUAN GAME ONLINE MELALUI LAYANAN KONSELING KELOMPOK - Prasetiawan, Hardi (STKIP Muhammadiyah Pringsewu, 2016)
This research is Classroom Action Research aims to reduce online gaming addictionthrough group counseling services. The methods used are questionnaires andobservation of the number of subjects studied were 10 students in two cycles , each cycleconsisting of three acts. Started from awarding the behavior contract as a form of writtenagreements for students to be responsible for the activities of group counseling and theprovision of a worksheet each after the counseling given as excavation problems andknowledge of students. The results showed that group counseling services through onlinegaming addiction in students can be reduced. It knowed before given the action thestudent is in the category of online game addiction as high as 10 people, after being givencounseling services group of 3 students in middle category and 7 low category.Keywords: Online Game Addiction, Group Counseling.